Harmonic Mitigation in Microgrid to Improve Power Quality - Widagdo, Reza Sarwo; Andriawan, Aris Heri; Hartayu, Ratna (Electrical Engineering, Universitas Mercu Buana, 2024)
Microgrids are a technology that is developing quite rapidly and is attracting world attention in facing the energy and pollution crisis. There are three types of microgrid structures: AC, DC, and AC-DC hybrid microgrid. Because it consists of an AC bus and a DC bus, AC-DC hybrid microgrids can connect more types of Distributed Generation (DG) and have smaller converter losses, making it more economical and reliable than other types of microgrids. Due to the use of nonlinear devices, harmonic distortion in microgrids is a problem that needs to be solved. In this research, the AC-DC hybrid microgrid system is simulated using ETAP software. Then the characteristics of the distribution of harmonics in the system obtained from harmonic load flow simulations are also analyzed. Following the installation of the passive filter, Bus 1 and Bus 2 now suitable to the IEEE Std standards 519-1992 for harmonic values. After the application of the filter, Bus 1 refer a THD of 1.32%, while Bus 2 indicate a THD of 0.84%. In addition, the Individual Harmonic Distortion (IHD) for Bus 1 has dropped below 3% at the 5th harmonic and below 1.5% at the 13th harmonic. Besides that, Bus 2 IHD has decreased to less than 3% at the 11th harmonic and less than 1.5% at the 13th harmonic.